Modeling a Simple Traveler Salesman Problem for Improving Energy Efficiency in Robots That Execute Computer Numerical Control Machining - Adasme-Soto, P; Morales-Diaz, C (Institute of Electrical and Electronics Engineers Inc., 2017)
Energy efficiency is a permanent concern in all types of production processes. The automation of machine tools using Computer Numerical Control (CNC) and the increasing introduction of manipulator robots mean a significant improvement in the efficient use of energy versus manual production methods, but there is still scope for improving efficiency and productivity. One of the methods to improve efficiency is the definition of optimal trajectories in the execution of automated tasks. In small and medium-scale flexible manufacturing systems, the tasks assigned to CNC machines are usually given in standardized formats, such as G-code, where the paths defined from the design software do not necessarily take into account the efficient use of the energy for a given machine. This problem is addressed in this paper from the need to optimize the use of energy in an articulated robot that performs a drilling task originally designed to be executed in a CNC drill. We propose a simple method to model the energy consumption of the robot as an optimization problem in the well-known form of a Traveler Salesman Problem (TSP), with which it is possible to use common software packages for its resolution. The proposed solution simplifies the approach of the optimization problem in relation to other proposals in the literature and is generalizable to other machining tasks and machining systems. © 2017 IEEE.